2018
DOI: 10.7600/jpfsm.7.113
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of physical activity promotion, physical activity, and sedentary behavior in elderly Japanese

Abstract: This study describes relationships between awareness of physical activity (PA) promotion and duration of PA and sedentary behavior (SB) in elderly Japanese. Following a community-wide intervention, 874 individuals 65 years or over were selected via population-based random sampling of 3,000 adults aged 20 years or over living in Fujisawa City, and asked to complete self-administered questionnaires; 550 responded and 373 with data on pertinent variables were included. Forty-eight percent (179/373) stated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Older adults who have a history of falls tend to have significantly lower muscle strength in their hip musculature [22]. PA has been shown to improve muscular strength and balance, and, therefore, reduce the risk of falls among the elderly [42]. Research has identified two main types of VR-based exercises that are related to older adults' reduced fall rates: VR-based treadmill exercises and Wii Fit exercises.…”
Section: Effects Of Vr On Rehabilitative Outcomes In Older Adultsmentioning
confidence: 99%
“…Older adults who have a history of falls tend to have significantly lower muscle strength in their hip musculature [22]. PA has been shown to improve muscular strength and balance, and, therefore, reduce the risk of falls among the elderly [42]. Research has identified two main types of VR-based exercises that are related to older adults' reduced fall rates: VR-based treadmill exercises and Wii Fit exercises.…”
Section: Effects Of Vr On Rehabilitative Outcomes In Older Adultsmentioning
confidence: 99%
“…[5] Thorough and appropriate assessment of the elderly individual is critical to the development of intervention strategies directed toward risk reduction and health promotion. [6,7] A major goal of health promotion program in senior housing is promoting physical activity for older residents. [8][9][10][11] Difficulties or threats to this empowerment program was that this program empowered the elderly, where special methods are needed to deliver material so that they can easily receive the material.…”
Section: Discussionmentioning
confidence: 99%
“…The first and second authors judged these free responses as correct, classified as “aware,” or incorrect. Prompted recall is a method to evoke the participants' memory by presenting hints, such as options or pictures, and asking them to respond [ 18 , 22 , 30 ]. For this recall, two types of recall were used: written and illustrated recalls.…”
Section: Methodsmentioning
confidence: 99%
“…In the illustrated recall, we presented an illustration of the Active Guide and asked the participants to respond either “yes” or “no” if they had ever seen or heard of a campaign that encouraged them to exercise or move their bodies. Those who answered “yes” were classified as “aware” [ 22 ]. Finally, we defined those who recognized any of the recall as “aware” of the PA guidelines.…”
Section: Methodsmentioning
confidence: 99%